Rancang Bangun Aplikasi Customer Relationship Management (CRM) Berbasis Web untuk Pengelolaan Data Pelanggan pada PT Winka Karisma Gemilang QQ Edwin Bright Property - Fathir Maulana Assyifa; Farizi Ilham; Muhamad Faisal; Roby Amanda Putra Tamba (CV. Shofanah Media Berkah, 2026)
The development of information technology encourages companies to improve the effectiveness of customer data management and business processes digitally. PT Winka Karisma Gemilang QQ Edwin Bright Property still faces challenges in managing customer data manually through personal notes, instant messaging applications, and spreadsheet files, resulting in difficulties in data retrieval, sales agent monitoring, and customer communication management. This study aims to design and develop a web-based Customer Relationship Management (CRM) application to support integrated customer data management. The research methods employed include observation, interviews, literature review, and system development using the Waterfall methodology. The system was developed using PHP, MySQL, and Apache Web Server technologies. The results indicate that the CRM application is capable of managing customer data, property data, agent activities, sales pipelines, and sales reports in a centralized and structured manner. The implementation of the system improves sales process monitoring, enhances operational efficiency, and supports faster and more accurate decision-making.